أنضمام العراق لمنظمة التجارة العالمية الواقع والطموح (المجلة العراقية للعلوم الاقتصادية, 2018)
This research is a brief on the WTO and its impact on Iraq, and how it will support the entry process to increase trade between Iraq and the member states of the Organization, and how it will create jobs and new investments accelerated the movement of goods internationally for the benefit of traders and consumers alike, the goal is to improve the general benefit of the peoples of Member States to clarify what the most important challenges faced by Iraq since it seemed the negotiation stage and then join the WTO and what are the procedures to be followed to overcome these challenges.